POLITIK HUKUM PEMBUBARAN PARTAI POLITIK BERDASARKAN UNDANG-UNDANG NOMOR 24 TAHUN 2003 TENTANG MAHKAMAH KONSTITUSI - NOVRILA, YUTIKA; Indra, Mexsasai; HB, Gusliana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Legal Politics which is the direction of a legal policy made officially by the stateregarding laws that will be enforced or will not be enforced to achieve state goals within acertain period as well as a formal-procedural mechanism that determines whether or not thislaw-making procedure is legal can be related to legal development which cannot be separatedfrom the social reality that lives in a country. The dissolution of political parties is regulated inarticles 68 to 73 of Law no. 24 of 2003 concerning the Constitutional Court. As in other cases,in an application for the dissolution of a political party, there are three (3) possible decisionsthat will be handed down by the constitutional court, namely the application is declaredinadmissible, the application is granted and the application is decided within 60 days. If theconstitutional court is of the opinion that the petition does not meet the requirements. So thatresulted in weaknesses in the constitutional court, related to the existence of Legal Standingholders for proposing the dissolution of political parties which were only proposed by thegovernment. Until now, the Constitutional Court has never decided to disband a political partybecause it has never been brought to court.The purpose of this study is to find out an idea that there is a weakness in theConstitutional Court in the dissolution of political parties in Indonesia. This type of researchis normative in which the writer tries to collect and analyze bibliographical data as a writingsource which is divided into primary, secondary and tertiary data.The results of this study are that the dissolution of political parties is due to partyactivities that are contrary to Pancasila, and the 1945 Constitution of the Republic ofIndonesia. So that there is a weakness in the Constitutional Court in dissolving politicalparties, which no longer fulfills the requirements determined by laws and regulations anddoes not carry out its obligations and does not carry out its functions in accordance withapplicable laws and regulations, in laws and regulations, legal politics has a very importantrole as a necessary reason in the formation of a statutory regulation and becomes aformulation in articles. Indonesia is a democratic country that must uphold democratic valuesand the concept of law must have an obligation to guarantee legal order, guarantee theupholding of a law as a prosperous socio-economic concept for service.Keywords: Legal Politics - Constitutional Court - Dissolution of Political Parties